Field reports form for submitting seasonal observations of Iowa birds, Douglas C. Harr, fall 1987 - Harr, Douglas C.et al (1987)
Fall report of birds found in northwest Iowa contributed by Douglas C. Harr. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1987. Epson - sheet feed